Regional Hydroclimatic Variability Due To Contemporary Deforestation in Southern Amazonia and Associated Boundary Layer Characteristics. Issue 8 (26th April 2018) - Khanna, Jaya; Medvigy, David; Fisch, Gilberto; de Araújo Tiburtino Neves, Theomar Trindade
Abstract: Amazonian deforestation causes systematic changes in regional dry season precipitation. Some of these changes at contemporary large scales (a few hundreds of kilometers) of deforestation have been associated with a "dynamical mesoscale circulation, " induced by the replacement of rough forest with smooth pasture. In terms of decadal averages, this dynamical mechanism yields increased precipitation in downwind regions and decreased precipitation in upwind regions of deforested areas. Daily, seasonal, and interannual variations in this phenomenon may exist but have not yet been identified or explained. This study uses observations and numerical simulations to develop relationships between the dynamical mechanism and the local‐ and continental‐scale atmospheric conditions across a range of time scales. It is found that the strength of the dynamical mechanism is primarily controlled by the regional‐scale thermal and dynamical conditions of the boundary layer and not by the continental‐ and global‐scale atmospheric state. Lifting condensation level and wind speed within the boundary layer have large and positive correlations with the strength of the dynamical mechanism. The strength of these relationships depends on time scale and is strongest over the seasonal cycle. Overall, the dynamical mechanism is found to be strongest during times when the atmosphere is relatively stable. Hence, for contemporary large scales of deforestation this phenomenon is found to be the prevalent convective triggering mechanism during the dry and parts of transition seasons (especially during the dry‐to‐wet transition), significantly affecting the hydroclimate during this period. Key Points: Contemporary Amazonian deforestation causes a regional spatial redistribution of precipitation during the local dry and transition months This phenomenon is controlled by and is positively correlated with regional conditions like boundary layer stability and wind speed This control of boundary layer conditions on precipitation redistribution is robustly observed at daily and seasonal time scales